Manusia Silver dan Seni Jalanan: Manifestasi Ruang Kebebasan Bagi Masyarakat di Perkotaan : 1*Rahman Malik, 2Achmad Hidir,3Nurainun Silalahi,4Salsabila Aulia Rahmi 1*,3,4 Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Sumatera Utara, Indonesia 2 Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, Indonesia - Rahman Malik; Achmad Hidir; Nurainun Silalahi; Salsabila Aulia Rahmi (Jurnal Intervensi Sosial, 2023)
Abstract The complexity of life and problems in urban areas have given birth to many phenomena of urban society, including the presence of silver men. However, as economic conditions deteriorate, especially due to the Covid-19 pandemic, many people have the initiative to adopt the “silver man style” as an opportunity to earn their personal money. Therefore, this research aims to examine how silver people express art as a form of their freedom space living in urban society. This research is a descriptive qualitative research method. The subjects of this research are silver men who are present in the area Dr.Mansur Street, Medan City. Primary data sources in this study were generated through observations and interviews with silver men. Meanwhile, secondary data was generated by digging up information about silver men in Medan City through book documentation, journals, and internet websites. The technique of data analysis is by conducting an interactive model of data analysis form Miles & Huberman. The results of this study show that urban public space is a place of freedom for silver men in Medan City to show their existence of expression of freedom to the general public. Forms of expression and existence of silver humas in Medan City include silver humans, very free to perform pantonymous forms of attraction and style like robots. Then, silver mens can easily collect money from the results of their labour by performing silver men attractions withput any social structure or environment that suppresses them to express and show their existence in the space of freedom or urban public space. Keyword: Silver men, Urban, Public space, Freedom of space, Street performance